Judicial activism in India: a frestschrift in honour of Justice V.R. Krishna Iyer - Malik, Lokendra (ed.) (New Delhi, 2013)
This book contains a socio-political study of judicial review, tracing the evolution of the Supreme Court of India from a passive, positivist court into an activist articulating counter majoritarian checks on democracy.
Keywords: Political questions and judicial power-India